(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article is devoted to the life path, creative heritage and works of Navoi scholar Rahim Vahidov. The scientist’s great services in the field of study, research and Navoi studies of Alisher Navoi’s work are specially recognized. In the classic text analysis, the skill of using words is analyzed.